OPTIMIZING CROSS-SECTORAL REPRODUCTIVE HEALTH EDUCATION ACTIVITIES TO PREVENT EARLY MARRIAGE IN BANYAKAN DISTRICT - Widhi Sumirat; Nugrahaeni Firdausi (Suluh Adiluhung Publisher (SAPub), 2026)
Optimizing cross-sectoral reproductive health education activities, by involving various stakeholders, such as the health sector, but also education, religion, local government, TNI/POLRI, Community Organizations, increases the effectiveness of early marriage prevention. The purpose of this study is to provide a comprehensive overview of the effectiveness of a cross-sectoral approach in reproductive health education for elementary and junior high school students in the Banyakan District area. This type of research is qualitative research with a descriptive analytical approach. The population in this study were students in grades 5-6 in 12 elementary schools and grades 7-8 in 1 junior high school in Banyakan District, using a total sampling technique. Data collection was carried out from November 12 to 19, 2025, with questionnaires before health education and one day after health education was conducted. The results of the study showed that before health education, the average knowledge score of elementary school participants only reached 28%, and junior high school participants 41%, while after participating in health education, there was a significant increase, with the average post-test score of elementary school participants increasing to 53%, while junior high school participants increased to 81%. This illustrates that optimizing cross-sectoral reproductive health education activities with early marriage prevention is very effective, so it is recommended that optimizing cross-sectoral reproductive health education can be used as an internal guideline in early marriage prevention programs.